STAT Inhibitors in Cancer - Ward, Alister C. (Cancer Drug Discovery and Development, 2016)
This volume, which includes contributions from leading scientists and clinicians in the field, provides definitive, state-of-the-art information on STAT inhibitors in a biological and clinical context. It gives an overview of the biology of the STAT family of transcription factors and their role in cancer etiology. Additionally, it describes the raft of therapeutic approaches being used to inhibit STATs in the context of various cancers, covering the full spectrum of therapeutic approaches to inhibiting STATs, and presenting emerging data from clinical trials.